Genetic parameters of color phenotypes of black tiger shrimp (Penaeus monodon) - Hasan, Md. Mehedi; Raadsma, Herman W.; Thomson, Peter C.; Wade, Nicholas M.; Jerry, Dean R; Khatkar, Mehar S. (Frontiers in Genetics, 2022)
Black tiger shrimp (Penaeus monodon) is the second most important aquaculture species of shrimp in the world. In addition to growth traits, uncooked and cooked body color of shrimp are traits of significance for profitability and consumer acceptance. This study investigated for the first time, the phenotypic and genetic variances and relationships for body weight and body color traits, obtained from image analyses of 838 shrimp, representing the progeny from 55 sires and 52 dams. The color of uncooked shrimp was subjectively scored on a scale from 1 to 4, with “1” being the lightest/pale color and “4” being the darkest color. For cooked shrimp color, images of cooked color were regraded on a three-point scale from brightest and lightest colored cooked shrimp, to darkest and most color-intense, with a high repeatability (r = 0.80 to 0.92). Objective color of both cooked and uncooked color was obtained by measurement of RGB intensities (values range from 0 to 255) for each pixel from each shrimp and converted to L*a*b* (CIE Lab) systems of color properties. In total, eight color-related traits were investigated. An ordinal mixed (threshold) model was adopted for manually (subjectively) scored color phenotypes, whereas all other traits were analyzed by linear mixed models using ASReml software to derive variance components and estimated breeding values (EBVs). Moderate to low heritability estimates (0.05 to 0.35) were obtained for body color traits. For subjectively scored cooked and uncooked color, EBV-based selection would result in substantial genetic improvement in these traits. The genetic correlations among cooked, uncooked and body weight traits were high and ranged from -0.88 to 0.81. These suggest for the first time that (i) cooked color can be improved indirectly by genetic selection based on color of uncooked/live shrimp, and (ii) intensity of coloration is positively correlated with body weight traits and hence selection for body weight will also improve color traits in this population.